Russia on the Danube : empire, elites, and reform in Moldavia and Wallachia, 1812-1834 - Taki, Viktor (Historical studies in Eastern Europe and Eurasia, 2021)
"One of the goals of Russia's Eastern policy was to turn Moldavia and Wallachia, the two Romanian principalities north of the Danube, from Ottoman vassals into a controllable buffer zone and a springboard for future military operations against Constantinople. Russia on the Danube describes the divergent interests and uneasy cooperation between the Russian officials and the Moldavian and Wallachian nobility in a key period between 1812 and 1834. The main conclusion of the book is that although Russian policy was driven by self-interest, and despite the Russophobia among a great part of the Romanian intellectuals, this turbulent period significantly contributed to the emergence, several decades later, of modern Romania"--